Online learning during the covid-19 pandemic: How is it implemented in elementary schools? - Azmil Hasan Lubis; Muhammad Darwis Dasopang (Universitas PGRI Madiun, 2021)
The Covid-19 pandemic that occurred forced the learning process to be carried out online or online learning. This study aims to analyze the opportunities and challenges of teachers and students who carry out the online learning process during the Covid-19 pandemic. This research uses a qualitative approach with a case study type. The subjects of this research were class teachers and grade IV elementary school students. The sampling technique used was purposive random sampling. Data collection techniques used interviews and documentation. The data obtained in this study were qualitative data which were analyzed using data triangulation techniques. The results showed that teachers and students got several opportunities and challenges implementing the online learning process during the Covid-19 pandemic. The opportunities for elementary school teachers and students are (1) Technology ability, (2) more accessible learning, (3) expanding learning references. Meanwhile, the challenges faced by elementary school teachers and students in online learning during the Covid-19 pandemic were (1) difficulty achieving learning objectives, (2) network disruption, (3) high cost.